The language of corruption and informality in Albanian: lexical semantics meets the social and political sciences - Skenderi, Elsa; Hansen, Björn (Comparative Legilinguistics, 2025)
Corruption is an omnipresent concept in public discourse and a significantly researched topic, yet there is little research on how people speak about corruption or how corruption is framed, a factor that we believe to be central to the understanding of corrupt practices. The present paper employs a lexical-semantic approach to the language of corruption in Albania. Firstly, a short overview of linguistic work dealing with aspects of discourses on corruption is given. Then, the paper focuses on certain sociological and economic approaches to corruption and informality. This last concept and Agency Theory (Principal-Agent Theory) are combined to examine corruption, through frame semantics approach. Further, a prolific inventarisation of the Albanian lexicon of corruption, as reflected in lexicographic sources and reference corpus, is delivered in the paper. Lastly, several petty corruption cases from the Albanian press are analyzed to understand better how corruption is framed linguistically. From a conceptual metaphor perspective, corruption is negatively conceptualized, as is the case in other European languages too, whereas, from a frame semantic perspective, there seems to be a lack of moral evaluation in reporting petty corruption cases.